Ganjar Pranowo's Image Politics Through TikTok Content Videos - Hendra Hidayat; Nani Nurani Muksin (Ikatan Sarjana Komunikasi Indonesia, 2022)
The internet penetration rate in Indonesia reached 77.02% in the first quarter of 2022. The internet and social media are suitable media for the process of communication and political campaigns. With the growing number of users, social media TikTok becomes a new strategic tool for politicians to drive political narratives. One of the Indonesian politicians and state officials who use TikTok social media is Ganjar Pranowo, who is currently serving his second term as Governor of Central Java (2013-2023). Ganjar Pranowo was selected for review because of his electability in the top three positions in June 2022. This article aims to: 1) find out and analyze the politics of Ganjar Pranowo's image on the TikTok account @ganjarpranowofc by exploring the meaning of the messages contained in it; and 2) interpret the political image it displays through the impression received by the audience. This article was compiled using a descriptive qualitative method with a semiotic analysis approach model from Roland Barthes on the video content of the @ganjarpranowofc TikTok account. The results found: that video content was uploaded as a strategy for shaping Ganjar Pranowo's political image. The messages in the video show Ganjar Pranowo's charm who is close to the people, does actual work, balances world life with spirituality, shows social empathy, is friendly to the issue of diversity-child-women and is responsive to up-to-date issues. The uploaded videos also show the figure of Ganjar Pranowo, who enjoys his job as a governor who serves the community. The visual strategies used include 1) biographical strategy, 2) incumbent strategy, and 3) the strategy of the Head of Kagama. TikTok account @ganjarpranowofc is also managed professionally from pre-production to post-production.Â